Health-related quality of life assessed by the EORTC QLQ-C30 questionnaire in the general Slovenian population - Velenik, Vaneja (Radiology and oncology (Ljubljana), 2017)
The aim of our study was to obtain reference data of the EORTC QLQ-C30 quality of life dimensions for the general Slovenian population. We intend to provide the researchers and clinicians in our country with the expected mean health-related quality of life (HRQL) scores for distinctive socio-demographic population groups. Methods. The EORTC QLQ-C30 questionnaire supplemented by a socio-demographic inquiry was mailed or distributed to 1,685 randomly selected individuals in the Slovenian population aged 18 % 90. Answers from 1,231 subjects representing socio-demographic diversity of the Slovenian population were collected and transformed into EORTC dimensions and symptoms. The impact of socio-demographic features on HRQL scores was assessed by multiple linear regression models. Results. Gender, age and self-rated social class are the important confounders in the quality of life scores in our population. Men reported better quality of life on the majority of the specific scales and, at the same time, reported fewer symptoms. There was no gender-specific difference in cognitive functioning. The mean scores were consistently lower with age in both sexes. Conclusions. This is the first study to report the normative EORTC QLQ-C30 scores for one of the south-eastern European populations. The reported expected mean scores allow Slovenian oncologists to estimate what the quality of life in cancer patients would be, had they not been ill. As they are derived by common methodology, our results can easily be included in any further international comparisons or in the calculation of European summarized HRQL scores.
Keywords: kakovost življenja; podatkovne baze; socio-demografski kazalniki; standard of living; zdravje